A fast sliding-mode-based estimation of state-of-charge for Lithium-ion batteries for electric vehicle applications. (January 2022) - Rezaei, Omid; Moghaddam, Hossein Azizi; Papari, Behnaz
Highlights: Accurate and robust observer for the state of charge estimation for lithium-ion battery Increasing the speed of the non-linear estimation Decreasing the chattering phenomena for a sliding mode-based observer Considering a complete equivalent circuit model including uncertainty for the battery Abstract: This paper present a 2- order fast embossing non-singular terminal sliding mode observer (2-FENSTSMO) for the state of charge (SoC) estimation of lithium-ion batteries. As these batteries have nonlinearities and uncertainties in their dynamic model, to estimate their SoC accurately a robust and nonlinear estimator is required. The sliding mode observers have chattering phenomena and prolong convergence time in their performance but the proposed observer tackles these problems and provides less chattering and convergence time. First, a second-order fast non-singular terminal manifold based on estimation error is defined, and then, according to the Lyapunov stability theory, in order to make a Lyapunov function descending, an appropriate control law is selected. An equivalent circuit model (ECM) for the battery including uncertainty is considered to design the proposed FNTSM observer. The stability of the proposed method is provided and the simulation and experimental results confirm the effectiveness of the proposed method. Graphical Abstract: Image, graphical abstract